Pregnancy complicated by central diabetes insipidus and oligohydramnios. Issue 8 (10th August 2021) - Imaizumi, Karin; Yasuda, Shun; Toba, Naoya; Okazaki, Takayuki; Fukuda, Toma; Murata, Tsuyoshi; Kann, Aya; Ishibashi, Makiho; Kyozuka, Hyo; Ito, Fumihiro; Yamaguchi, Akiko; Fujimori, Keiya
Abstract: This is the fourth reported case of central diabetes insipidus with oligohydramnios. Central diabetes insipidus does not adversely affect pregnancy; it can present with oligohydramnios, which can be improved by treating central diabetes insipidus. Abstract : This is the fourth reported case of central diabetes insipidus with oligohydramnios. Central diabetes insipidus does not adversely affect pregnancy; it can present with oligohydramnios, which can be improved by treating central diabetes insipidus.